MECHANISMS FOR MANAGING ELECTRONIC RESOURCES IN EDUCATIONAL PLATFORMS - Farrux Shokirov,; Mushtariy Saidova, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
This article examines the mechanisms for managing electronic resources in modern educational platforms, their classification, and practical implementation. The study analyzes the functional capabilities of Learning Management Systems (LMS), resource cataloging methods, access control models, and digital content quality assurance mechanisms. The research findings are summarized with practical recommendations for the effective management of electronic resources in educational institutions of Uzbekistan.